Peran Supervisi Pendidikan dalam Meningkatkan Kualitas Pengajaran dan Pembelajaran di SD 089 Panyabungan - Nur Asiah; Novebri Novebri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Educational supervision in elementary schools is an activity to improve the quality of learning in elementary schools. Educational supervision must also adapt to existing technological developments. For its implementation, supervision is carried out through various processes in the aspect of problem solving that aims to increase teacher effectiveness and efficiency. In addition, it also functions to improve the quality of learning in Indonesia which until now has not met the standards and is far from what is expected. The role of supervision here is responsible for improving teacher learning by following the development of science and technology and the use of supervision techniques. Based on the results of the data analysis, it was obtained that Educational Supervision has a role in the quality of teaching. In this article, the literature study method is used. This article will discuss the role of educational supervision in improving the quality of learning. This article will discuss the definition of educational supervision, the role of educational supervision in improving the quality of learning. The implementation of supervision is expected to run well so that the implementation of learning. Therefore, a supervisor needs to have an understanding and awareness of educational supervision. This article aims to describe the concept of educational supervision to improve the quality of learning in the era of independent learning. This study aims to analyze the role of supervision in improving the quality of continuous learning at SD 089 PANYABUNGAN. Identification of potential and individual teacher needs through observation and coaching processes allows for the preparation of targeted professional development programs. Including. Implementation of innovative learning methods is encouraged through supervisory support that provides related resources and training.